Validation of Clinical Protocol of Astigmatism Induction in Pseudophakic Patients - De Melo Jnr IR; Hida WT; Moscovici BK; Vilar C; Motta AFP; de Medeiros AL; Chaves MAPD; Lake JC; Nose W; Carricondo PC (Clinical Ophthalmology)
Irineu Ribeiro De Melo Jnr,1 Wilson Takashi Hida,1– 3 Bernardo Kaplan Moscovici,4,5 Cesar Vilar,1,2 Antonio Francisco Pimenta Motta,1 Andre Lins de Medeiros,1 Mario Augusto Pereira Dias Chaves,1 Jonathan Clive Lake,1 Walton Nose,4 Pedro Carlos Carricondo3 1Department of Ophthalmology, Hospital Oftalmológico De Brasília, Brasília, DF, Brazil; 2Department of Ophthalmology, Renato Ambrosio Eye Research Center, Brasília, DF, Brazil; 3Department of Ophthalmology, University of Sao Paulo, São Paulo, SP, Brazil; 4Department of Ophthalmology, Federal University of Sao Paulo UNIFESP, São Paulo, SP, Brazil; 5Department of Ophthalmology, Hospital Visão Laser, Santos, SP, BrazilCorrespondence: Bernardo Kaplan Moscovici, Email bernardokaplan@yahoo.com.brPurpose: Validate a novel approach for assessing residual astigmatism’s impact on visual acuity in pseudophakic patients using defocus curves and spherical equivalent compensation.Materials and Methods: Thirteen patients over 40 with cataracts and normal ophthalmological examinations were enrolled in a prospective, non-randomized cohort study. The defocus curve method was employed, wherein visual acuity was measured with spherical lenses ranging from − 2.50 to +2.50 diopters in 0.5 diopter increments based on subjective refraction. Cylindrical lenses (+1, +2, and +3 diopters) were introduced at each spherical diopter’s 90° and 180° axes. Curves’ results were compared at each defocus point to assess the impact of astigmatism. The Kruskal–Wallis test was used to determine if astigmatism significantly affected visual acuity post-phacoemulsification surgery with intraocular lens implantation.Results: Significant p-values were observed only for defocus curve points of − 0.5, 0, +0.5, and +1, indicating rejection of the hypothesis of no difference between the 90° and 180° groups at these points. Although statistical significance was not achieved, the against-the-rule (ATR) group was inclined toward improved near and intermediate visual acuity. In contrast, the with-the-rule (WTR) group tended to enhance distance visual acuity and myopic tolerance.Conclusion: This novel methodology is both reproducible and valuable. It offers potential insight into residual astigmatism tolerance in pseudophakic patients. Its application may aid in surgical planning and intraocular lens decision-making.Keywords: cataract, astigmatism, visual acuity, treatment result